Connectivity of sleep- and wake-promoting regions of the human hypothalamus observed during resting wakefulness. Issue 9 (29th May 2018) - Boes, Aaron D; Fischer, David; Geerling, Joel C; Bruss, Joel; Saper, Clifford B; Fox, Michael D
Abstract: The hypothalamus is a central hub for regulating sleep–wake patterns, the circuitry of which has been investigated extensively in experimental animals. This work has identified a wake-promoting region in the posterior hypothalamus, with connections to other wake-promoting regions, and a sleep-promoting region in the anterior hypothalamus, with inhibitory projections to the posterior hypothalamus. It is unclear whether a similar organization exists in humans. Here, we use anatomical landmarks to identify homologous sleep- and wake-promoting regions of the human hypothalamus and investigate their functional relationships using resting-state functional connectivity magnetic resonance imaging in healthy awake participants. First, we identify a negative correlation (anticorrelation) between the anterior and posterior hypothalamus, two regions with opposing roles in sleep–wake regulation. Next, we show that hypothalamic connectivity predicts a pattern of regional sleep–wake changes previously observed in humans. Specifically, regions that are more positively correlated with the posterior hypothalamus and more negatively correlated with the anterior hypothalamus correspond to regions with the greatest change in cerebral blood flow between sleep–wake states. Taken together, these findings provide preliminary evidence relating a hypothalamic circuit investigated in animals to sleep–wake neuroimaging results in humans, with implications for our understanding of human sleep–wake regulation and the functional significance of anticorrelations.